Rice research to break yield barriers - Verma, Vivek; Ramamoorthy, Rengasamy; Kohli, Ajay; Kumar, Prakash P. (World Scientific Publishing, 2015)
The world’s population continues to expand and it is expected to cross 9 billion by 2050. This would significantly amplify the demand for food, which will pose serious threats to global food security. Additional challenges are being imposed due to a gradual decrease in the total arable land and global environmental changes. Hence, it is of utmost importance to review and revise the existing food production strategies by incorporating novel biotechnological approaches that can help to break the crop yield barriers in the near future. In this review, we highlight some of the concerns hampering crop yield enhancements. The review also focuses on modern breeding techniques based on genomics as well as proven biotechnological approaches that enable identification and utilization of candidate genes. Another aspect of discussion is the important area of research, namely hormonal regulation of plant development, which is likely to yield valuable regulatory genes for such crop improvement efforts in the future. These strategies can serve as potential tools for developing elite crop varieties for feeding the growing billions.